The Evolution of Oxytocin and Vasotocin Receptor Genes in Jawed Vertebrates: A Clear Case for Gene Duplications Through Ancestral Whole-Genome Duplications - Ocampo Daza, Daniel; Bergqvist, Christina A.; Larhammar, Dan (Frontiers in Endocrinology, 2022)
The neuronal and neuroendocrine peptides oxytocin (OT) and vasotocin (VT), including vasopressins, have six cognate receptors encoded by six receptor subtype genes in jawed vertebrates. The peptides elicit a broad range of responses that are specifically mediated by the receptor subtypes including neuronal functions regulating behavior and hormonal actions on reproduction and water/electrolyte balance. Previously, we have demonstrated that these six receptor subtype genes, which we designated VTR1A, VTR1B, OTR, VTR2A, VTR2B and VTR2C, arose from a syntenic ancestral gene pair, one VTR1/OTR ancestor and one VTR2 ancestor, through the early vertebrate whole-genome duplications (WGD) called 1R and 2R. This was supported by both phylogenetic and chromosomal conserved synteny data. More recently, other studies have focused on confounding factors, such as the OTR/VTR orthologs in cyclostomes, to question this scenario for the origin of the OTR/VTR gene family; proposing instead less parsimonious interpretations involving only one WGD followed by complex series of chromosomal or segmental duplications. Here, we have updated the phylogeny of the OTR/VTR gene family, including a larger number of vertebrate species, and revisited seven representative neighboring gene families from our previous conserved synteny analyses, adding chromosomal information from newer high-coverage genome assemblies from species that occupy key phylogenetic positions: the polypteriform fish reedfish (Erpetoichthys calabaricus), the cartilaginous fish thorny skate (Amblyraja radiata) and a more recent high-quality assembly of the Western clawed frog (Xenopus tropicalis) genome. Our analyses once again add strong support for four-fold symmetry, i.e., chromosome quadruplication in the same time window as the WGD events early in vertebrate evolution, prior to the jawed vertebrate radiation. Thus, the evolution of the OTR/VTR gene family can be most parsimoniously explained by two WGD events giving rise to the six ancestral genes, followed by differential gene losses of VTR2 genes in different lineages. We also argue for more coherence and clarity in the nomenclature of OT/VT receptors, based on the most parsimonious scenario.